2009
DOI: 10.1523/jneurosci.3233-09.2009
|View full text |Cite
|
Sign up to set email alerts
|

Associatively Learned Representations of Taste Outcomes Activate Taste-Encoding Neural Ensembles in Gustatory Cortex

Abstract: Through learning processes, cues associated with emotionally salient reinforcing outcomes can come to act as substitutes for the reinforcer itself. According to one account of this phenomenon, the predictive cue associatively elicits a representation of the expected outcome by reactivating cells responsible for encoding features of the primary reinforcer. We tested this hypothesis by examining the role of neural ensembles in gustatory cortex (GC) during receipt of gustatory stimuli (sucrose and water) and cues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
63
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(71 citation statements)
references
References 51 publications
7
63
1
Order By: Relevance
“…Sparse, discrete units were detected, sometimes with dendritic immunoreactivity (data not shown). Cell counting analysis on saccharin-drinking animals revealed that on average, 22.28% of neurons were found to be Arc+ after novel (N) taste (263 + 44 neurons/animal, n ¼ 5) and 20.67% after familiar (F5) taste (288 + 38 neurons/animal, n ¼ 5), both figures being very similar to what has been reported in other studies on taste learning that evaluated Arc mRNA levels (Barot et al 2008;Saddoris et al 2009). When comparing the percentage of neurons expressing Arc protein in both conditions, no difference was detected between N and F5 (t (8) ¼ 0.96, P ¼ 0.37), indicating that the same proportion of neurons were activated in the IC by a familiar and a novel taste stimulus (Fig.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Sparse, discrete units were detected, sometimes with dendritic immunoreactivity (data not shown). Cell counting analysis on saccharin-drinking animals revealed that on average, 22.28% of neurons were found to be Arc+ after novel (N) taste (263 + 44 neurons/animal, n ¼ 5) and 20.67% after familiar (F5) taste (288 + 38 neurons/animal, n ¼ 5), both figures being very similar to what has been reported in other studies on taste learning that evaluated Arc mRNA levels (Barot et al 2008;Saddoris et al 2009). When comparing the percentage of neurons expressing Arc protein in both conditions, no difference was detected between N and F5 (t (8) ¼ 0.96, P ¼ 0.37), indicating that the same proportion of neurons were activated in the IC by a familiar and a novel taste stimulus (Fig.…”
Section: Resultssupporting
confidence: 85%
“…Also, in vivo intrinsic imaging experiments showed that the anterior part of the IC responded best to taste modalities (Accolla et al 2007). Further, a more recent study using neuronal activity mapping with Arc mRNA (Saddoris et al 2009) indicates that the integration of taste-related information mostly occurs in the anterior dysgranular region of the IC. Finally, based on early electrophysiological evidence (Yamamoto et al 1989), as well as in preliminary findings from our lab with Arc immunohistochemistry, we determined that layers IV/V best responded to taste stimulation.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies using rats have shown that neurons in the IC can change their firing in response to auditory cues anticipating the availability of taste (26,29,30). To determine whether IC activity could also be modulated by anticipatory cues in the present experimental conditions, we implanted 14 mice with movable bundles of 8 or 16 electrodes.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, food-paired CSs can activate the gustatory region of the insular cortex (GC) in both rodents (Dardou et al 2006(Dardou et al , 2007 and humans (Veldhuizen et al 2007;Small et al 2008). Importantly, these CSs activate the very same neuronal ensembles in the GC that were activated by the food US itself, providing a neural substrate of CS retrieval of a reward representation (Saddoris et al 2009). …”
Section: Circuitry Of Outcome Representationsmentioning
confidence: 99%